The Political Economy of Cordon Tolls - Antonio Russo; Bruno De Borger (European Regional Science Association (ERSA), 2015)
Political acceptability is the primary obstacle to implementation of road pricing in many cities. This paper studies the political economy of urban road pricing in its most common incarnation: cordon tolling. We relate voters? preferences for the road toll to its impact on the city?s land market. We consider a monocentric city inhabited by pure renters and resident landowners. The price of land within (resp. outside) the cordon increases (decreases) with the toll. Hence, tolling redistributes welfare not only from renters to landowners, but also within landowners. We show that the majority voting equilibrium depends both on the extent to which land is owned by residents and on which part of the city the majority owns land in. The equilibrium toll can be equal or higher than the socially optimal level only if the majority of city residents own land within the cordon. Otherwise, the majority always votes for a toll smaller than the optimal level or even no toll at all. If residents have heterogeneous wages, the above results are confirmed as long as the median individual has a smaller wage than the average.
Keywords: R41; D78; H23; 330; cordon tolls; road pricing; voting; monocentric city